Application of Kendall's rank function for digital image correlation. (1st March 2019) - Liu, Siqi; Tu, Peihan; Xu, Weichao; Xie, Shengli; Wu, Weizeng; Zhang, Yang; Zhou, Yanzhou
Abstract: Digital image correlation (DIC) is a widely used technique for measuring the surface deformation of solid materials and structures. A new criterion, called Kendall's rank correlation function (KRCF), has been applied to replace the traditional Pearson's product moment correlation function (PPMCF), which is a zero-mean normalized cross-correlation criterion in essence. By comparing the rank information of the reference and target subsets, the difference between the concordant and discordant pairs is larger and their correlation is higher. Simulations and experiments show that the performance of KRCF is better than PPMCF in an environment with: (1) salt-and-pepper noise; (2) monotone nonlinear light intensity distortion; (3) a fixed bright spot; and (4) cracks.